Blueprint for progress: Understanding the driving forces of BIM adoption in Kingdom of Saudi Arabia (KSA) construction industry. - Muzaffar Iqbal; Irfan Ullah; Heba Abdou; Majed Alzara; Ahmed M Yosri (PLoS ONE)
Building information modeling (BIM) as a virtual and digital mode of representing construction activities gained significant attention and facilitated construction projects. Nevertheless, many driving forces (DFs) trigger the adoption of BIM. Different kinds of studies have been conducted regarding the DFs of BIM adoption in developed countries. However, few studies have classified the adoption of DFs of BIM technology in developing countries such as the Kingdom of Saudi Arabia (KSA). A range of previous literature identified these DFs in a different context, but there is a need to answer two main questions. First, what DFs could influence BIM adoption in the construction sector of (KSA); second, what could be the possible framework to prioritize these DFs. Therefore, Fuzzy Delphi Methodology (FDM), Interpretive structural modeling (ISM), and MICMAC were applied to answer these questions. Study results highlight that 'Reduced cycle time of the design process' and 'Efficient construction planning and management', are the main DFs to BIM adoption in the construction sector of (KSA). This study is the first to employ a hybrid FDM, ISM, and MICMAC approach to evaluate BIM implementation DFs in the KSA context. This study informs policymakers and industry practitioners in (KSA) to develop targeted strategies for effective BIM adoption. This study enhances collaboration and communication among construction industry stakeholders by understanding the significant DFs and their interrelationships.